2018
DOI: 10.25077/josi.v17.n2.p143-151.2018
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kepuasan Kerja dan Kinerja Karyawan

Abstract: Perusahaan Listrik Negara (PLN) is a public company engaged in serving electricity in Indonesia. The company is a state-owned company which has a lot of human resources both from the level of general education up to the highest level of education. The rapid development of industrialization and technological innovation makes the company must be more competitive in facing the increasing of fierce competition in the current era of globalization. This study aims to analyze and prove the influence of organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
0
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
5
0
0
8
Order By: Relevance
“…Representatives give high consideration to the workplace regarding solace, security, and focus at work. This is in accordance with research directed by (Eko Susetyo et al, 2014), (Wibowo et al, 2014), (Aruan and Fakhri, 2015), (OLDEMAR and Ibrahim, 2015), (Wuwungan et al, 2017), (Yudi Permadi and Suana, 2017), (Agustini et al, 2018), (Wahyuniardi et al, 2018), (Lumintang et al, 2019), (Junianto and Sabtohadi, 2019), (Krisnaldy et al, 2019), (Roy Sarlita Putra and Ayu Dewi Adnyani, 2019), (Virginita Orizanti et al, 2020), (Herdiana and Yuniasih, 2020), (Arifin, 2020), (Purnomo andTri Putranto, 2020), (Pranitasari andBela Saputri, 2020), (Damayanti and Ismiyati, 2020), (Saripuddin, n.d.), (Nofitasari and Prasetyo, 2021), (Hariani and Rahman Al Hakim, 2021), (Kurniyanto, 2022), (Derina Yusda et al, 2022), (Sudrajat et al, 2022), and (Sulistyawati et al, 2022 which expresses that the workplace impacts work fulfillment.…”
Section: The Influence Of Work Environment On Job Satisfactionsupporting
confidence: 89%
“…Representatives give high consideration to the workplace regarding solace, security, and focus at work. This is in accordance with research directed by (Eko Susetyo et al, 2014), (Wibowo et al, 2014), (Aruan and Fakhri, 2015), (OLDEMAR and Ibrahim, 2015), (Wuwungan et al, 2017), (Yudi Permadi and Suana, 2017), (Agustini et al, 2018), (Wahyuniardi et al, 2018), (Lumintang et al, 2019), (Junianto and Sabtohadi, 2019), (Krisnaldy et al, 2019), (Roy Sarlita Putra and Ayu Dewi Adnyani, 2019), (Virginita Orizanti et al, 2020), (Herdiana and Yuniasih, 2020), (Arifin, 2020), (Purnomo andTri Putranto, 2020), (Pranitasari andBela Saputri, 2020), (Damayanti and Ismiyati, 2020), (Saripuddin, n.d.), (Nofitasari and Prasetyo, 2021), (Hariani and Rahman Al Hakim, 2021), (Kurniyanto, 2022), (Derina Yusda et al, 2022), (Sudrajat et al, 2022), and (Sulistyawati et al, 2022 which expresses that the workplace impacts work fulfillment.…”
Section: The Influence Of Work Environment On Job Satisfactionsupporting
confidence: 89%
“…If the work environment used is clean, comfortable, healthy and pleasant then this will support employees to feel at home and comfortable in the work environment and more enthusiastic in completing their work [20]. This is in accordance with the results of research by [26], [12], [14] which showed the results of the work environment positively affect employee performance. Based on the above, the following hypothesis is proposed: H2: The work environment has a positive effect on employee performance The Effect of Organizational Culture on Employee Performance Organizational culture is a basic assumption such as beliefs, behavior and values created and developed by the organization as a basis for determining goals, achievements, innovation, integrity and used as a guideline for all members of the organization in behaving.…”
Section: The Effect Of Work Environment On Employee Performancesupporting
confidence: 77%
“…Dalam bekerja, kepuasan kerja karyawan dapat dipengaruhi oleh tempat atau lingkungan karyawan bekerja (Maslichah & Hidayat, 2017;Pangestu et al, 2017;Wahyuniardi et al, 2018). Hal ini karena setiap karyawan berharap memperoleh kepuasan dari tempatnya bekerja (Pangestu et al, 2017).…”
Section: Pendahuluanunclassified